Modular Construction educational at wall Painting Todevlop Skills Students using Tachnigue Airbrush Ihave students lnstite of fine Arts (Journal of the College of Basic Education, 2022)
In order to develop the educational process cognitively and skillfully and in order to elevate the learner, who is the focus of the educational process, it was necessary to exploit and develop all the techniques and means created by the products of the technological revolution, and in order to refine the energies and creations of man in various areas of life, especially the creative and artistic field. Building educational units in developing skills using Airbrush technology by refining and familiarizing students with the mechanism of using this technology in mural painting in order to train a generation capable of creating artistic creativity in different and new ways of formation.This research came under the title (building educational units in the subject of mural painting to develop students' skills using Airbrush technique among students of the Institute of Fine Arts)The current research aims to:- 1- Building educational units in the subject of mural painting to develop the skills of the students of the Institute of Fine Arts using the Airbrush technique.2- Recognizing the effect of educational units using the Airbrush technique on knowledge and skill achievement in the subject of murals.In order to achieve the second goal, the researcher put the following hypotheses:v The first null hypothesis (there are no statistically significant differences at the significance level (0.05) between the average ranks of the experimental group students' scores in the cognitive achievement test, before and after).v The second null hypothesis (there are no statistically significant differences at the significance level (0.05) between the average scores of the experimental group students in the pre and post skill performance test). In order to achieve the two hypotheses of the research, the researcher used the one-sample complete experimental design with the pre and post test to achieve the two objectives of the research and its hypotheses.The research community included students of the third stage / Department of Fine Arts / Drawing / Institute of Fine Arts / Boys / Diyala / second semester / for the academic year 2021-2022The researcher deliberately chose the sample consisting of (15) students as an experimental group for his research.After the construction of the educational units was completed and presented to the experts, and modifications were made to them, they were applied to the experimental sample. The information was collected and processed statistically by using the SPSS program. The results obtained were extracted, collected and discussed. Through the results, the researcher reached the following conclusions: -1- The components of the educational units in the subject of mural painting contributed to the students' (experimental) awareness of the topics that were taught according to the educational content, making it a purposeful, self-directed and collective process.2- The content of the educational units is distinguished by simplifying the learning process according to the information and concepts contained in the art of mural painting, which contributes to raising the aesthetic taste and artistic culture of the learner and the possibility of employing it in his artistic productions.